2000
DOI: 10.1080/713688934
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Tunica Intima of Varicose Veins: A Histopathological and Ultrastructural Study

Abstract: Many factors have been implicated in the aetiology of varicose veins; however, there is ample evidence implicating that the defect is in the wall of the lower limb veins. In order to know the pathological changes in the tunica intima of varicose veins, the smooth muscle cells (SMCs), collagen and elastin of varicose and control patients were studied by light and electron microscopy. The morphological changes in the SMCs, collagen and elastin point to a possible secretory or phagocytic role of the SMCs in produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
2
17
1
3
Order By: Relevance
“…On the other hand, the genetic predisposition of varicose veins, as evidenced by a strong family history in most affected patients [6], has been an impetus to identify abnormalities responsible for the disease [7]. Previous studies from our laboratory and others have demonstrated that mRNA expression and protein synthesis of collagen type I (collagen I) are increased in tissue media of varicose veins [1, 2, 8, 9]. The production of collagen III is reduced in varicose vein tissues [1] whereas mRNA expression is similar in control and varicose veins [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the genetic predisposition of varicose veins, as evidenced by a strong family history in most affected patients [6], has been an impetus to identify abnormalities responsible for the disease [7]. Previous studies from our laboratory and others have demonstrated that mRNA expression and protein synthesis of collagen type I (collagen I) are increased in tissue media of varicose veins [1, 2, 8, 9]. The production of collagen III is reduced in varicose vein tissues [1] whereas mRNA expression is similar in control and varicose veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that an abnormal remodeling occurs in varicose veins [1,2,3] and these alterations of the venous wall may be regarded as the primary cause of varicosis [4, 5]. Dilatations occur because the venous wall is weakened and valvular incompetence is secondary rather than primary [4].…”
Section: Introductionmentioning
confidence: 99%
“…Modifications in the media layer of the venous wall appear as general features of varicose veins. These modifications include ultrastructural signs of smooth muscle transition from a contractile to a metabolic phenotype, disturbed smooth muscle cell (SMC)/extracellular matrix (ECM) balance and loss of contractile properties of the venous wall [6,7,8,9,10,11]. ECM in the vascular wall provides an essential structural framework necessary for the maintenance of vascular integrity and cellular regulations such as tissue-specific gene expression, movement, differentiation and cell shape [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, collagen fibrils enter the area between the muscle fibers in the media layer, thereby disturbing the circular order of muscles (19,20). There is a decrease in the elastin fibers (10,18,21) and a fragmentation in the internal elastic lamina (13,18,20). However, there is an increase in other matrix proteins fibronectin, laminin and tenascin (18).…”
Section: Introductionmentioning
confidence: 97%
“…Although there are findings that show a decreased amount of collagen (7,8), the amount of collagen generally increases (9)(10)(11)(12)(13)(14)(15) and this situation is even observed in cellular cultures (15)(16)(17). The increase in collagen occurs both in the intima (13) and in the media (12,18). Furthermore, collagen fibrils enter the area between the muscle fibers in the media layer, thereby disturbing the circular order of muscles (19,20).…”
Section: Introductionmentioning
confidence: 99%